2021
DOI: 10.1016/j.cjca.2021.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes in Cardiovascular Trials

Abstract: Patient-reported outcomes (PROs) are reports of a person's health status that provide a global perspective of patient well-being. PROs can be classified into four primary domains: global, mental, physical, and social health. In this descriptive review, we focus on how PROs can be used in cardiac clinical trials, with an emphasis on cardiac surgical trials for patients with coronary heart disease and heart failure. We also highlight ongoing challenges and provide specific suggestions and novel opportunities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 116 publications
0
8
0
Order By: Relevance
“…Although many studies in this review used patient-reported outcome measures, the essential contribution of these data was ultimately “for research purposes only” to increase knowledge or to describe patient perspectives, expectations, or experiences. 203,204 A scoping review revealed 34 disease-specific patient-reported outcome measures for use with different cardiac conditions that have not been consistently integrated into clinical care despite the compelling ways in which these data could advance improvements in care. 204 This suggests the need to consider the opportunities for integrating and using these measures beyond research, in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies in this review used patient-reported outcome measures, the essential contribution of these data was ultimately “for research purposes only” to increase knowledge or to describe patient perspectives, expectations, or experiences. 203,204 A scoping review revealed 34 disease-specific patient-reported outcome measures for use with different cardiac conditions that have not been consistently integrated into clinical care despite the compelling ways in which these data could advance improvements in care. 204 This suggests the need to consider the opportunities for integrating and using these measures beyond research, in clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes will include health status, HRQoL and healthcare costs. We will include disease-specific and generic reports and measures of two patient-reported outcomes: health status (ie, worsening of the condition) and HRQoL (ie, perceived well-being measured using the Minnesota Living with Heart Failure, Kansas City Cardiomyopathy Questionnaire, 12-item short form survey (SF-12), EQ 5D value health instrument) 82. Estimating direct and indirect costs of peer support using a cost-effectiveness analysis, incremental cost-effectiveness ratio or quality-adjusted life-years will be included 83…”
Section: Methods and Analysismentioning
confidence: 99%
“…We will include disease-specific and generic reports and measures of two patient-reported outcomes: health status (ie, worsening of the condition) and HRQoL (ie, perceived well-being measured using the Minnesota Living with Heart Failure, Kansas City Cardiomyopathy Questionnaire, 12-item short form survey (SF-12), EQ 5D value health instrument). 82 Estimating direct and indirect costs of peer support using a costeffectiveness analysis, incremental cost-effectiveness ratio or quality-adjusted life-years will be included. 83 Systematically retrieve, screen and classify the evidence All team members, including women with lived experience, will participate in retrieving, screening and classifying the evidence.…”
Section: Identify Clear Eligibility Criteriamentioning
confidence: 99%
“…When captured rigorously, PRO results can aid in decisionmaking, systematic reviews, meta-analysis, and clinical guideline development and ultimately influence health care policy. 38 On an individual level, PROs provide a holistic picture of the consequences of the treatment or intervention and the impact it has on symptoms and quality of life. The Consensus-Based Standards for the Selection of Health Measurement Instruments checklist recommends using a multidomain approach for the measurement of PROs, including a selection of instruments across multiple domains and generic and disease-specific outcome assessments (Figure 2 and Supplemental Table S1).…”
Section: Patient-oriented Outcomesmentioning
confidence: 99%
“…When captured rigorously, PRO results can aid in decision-making, systematic reviews, meta-analysis, and clinical guideline development and ultimately influence health care policy. 38…”
Section: Patient-oriented Outcomesmentioning
confidence: 99%